Perkembangan Psikologis dan Kognitif Peserta Didik Kelas Rendah: Tinjauan Berdasarkan Teori Freud, Erikson, dan Piaget di SD Negeri 14 Koto Lalang - Alya Wira Pratiwi; Fammi Ramadhani; Hayatul Muslim Jamil; Muhammad Revaldi; Reysa Aulia Az-zahra; Dina Amsari (INDO PUBLISHING, 2026)
This study aims to analyze the psychological and cognitive development of second-grade students at Koto Lalang 14 Public Elementary School, Lubuk Kilangan District, West Sumatra, using three main developmental theories: Sigmund Freud's psychoanalytic theory, Erik Erikson's psychosocial theory, and Jean Piaget's cognitive development theory. The study employed a descriptive qualitative method with direct observation, interviews with classroom teachers, and documentation. Observations indicate that students aged 8–9 are in the latent stage (Freud's), the Industry vs. Inferiority stage (Erikson's), and the concrete operational stage (Piaget's). Findings indicate that students are able to work in groups and demonstrate logical thinking regarding concrete objects, but still experience difficulties with abstract concepts and occasionally display feelings of inferiority. This study recommends the implementation of concrete object-based learning, inclusive group activities, and positive feedback to support optimal student development.